SHARP – SPORTS MENTAL HEALTH AWARENESS RESEARCH PROJECT: PREVALENCE AND RISK FACTORS OF DEPRESSIVE SYMPTOMS AND LIFE STRESS IN ELITE ATHLETES. Issue 4 (1st February 2017) - Beable, Sarah; Fulcher, Mark; Hamilton, Bruce; Chun-Lee, Arier
Abstract : Background: Depression is a significant health issue. Recent athlete studies suggest depression is of similar prevalence to the general population, with risk factors such as retirement, concussion, and severe injury reported. The prevalence and identifiable risk factors amongst elite New Zealand athletes is unknown with no previous research in this field. Objective: To assess the prevalence of self-reported symptoms of depression and daily life hassles in elite New Zealand athletes. Design: A cross-sectional prospective epidemiological study. Setting: The online anonymous survey was administered during a 2-month period from May to July 2015. Patients (or Participants): All current NZ athletes>18 years from funded sports invited. 210 started the questionnaire, with 187 completing all responses. Only complete responses analysed. Main Outcome Measurements: Demographic and health history obtained. Symptoms of depression were measured by the Centre for Epidemiological Studies Depression Scale- Revised (CESD-R). Life stress measured by the Daily Hassles Questionnaire. Results: 21% (n=39) reported symptoms of moderate depression. Of these 40% met the criteria for a Major Depressive Episode. Only 2 of the 39 athletes were currently taking an anti-depressant medication. Those contemplating retirement, and partaking in individual sport had significantly increased odds of experiencing depression with young age also associated. Reported life stressors were higher in females, individual sports, those in partial employment and in a centralized programme. Troubling thoughts about their future, and concerns about meeting high standards were the highest reported life stress. There was a significant correlation between higher level of life stress and experiencing depressive symptoms Conclusion: This study supports that depressive symptoms are prevalent in elite New Zealand athletes. Multiple risk factors have been identified pertaining to symptoms of depression and life stressors. These concepts and variables warrant further exploration to enable appropriate screening and support for elite athletes.